KETERCAPAIAN IMPLEMENTASI KURIKULUM 2013 DI MASA PANDEMI COVID-19 - Roberto W. Marpaung; Serlina Boru Sinaga (Program Studi PGSD Universitas Flores, 2022)
The issue of decreasing knowledge of nationalism of the senior high students in Papua had been the background of this research. The Covid-19 Pandemic has impacted various sectors, especially in education. More research are needed to figure out the education implementation during the pandemic so that appropriate policies can then be formulated and issued. This research was aimed at describing the implementation of 2013 Curriculum during the pandemic on Civics. It was carried out at SMA Negeri 2 Merauke. The research design applied was a descriptive with qualitative method. Three data collection techniques were used; interviews, observations, and documentation. The respondents of research consisted of principal, vice principal for curriculum, Civics teacher, and school administration officer. The data analysis was carried out by following several stages, such as data presentation, data reduction, and conclusion. The result showed that the implementation of Curriculum 2013 on Civics during the Pandemic Covid-19 was not effective. It was also not suitable with the the emergency condition as Covid-19. Long distance learning model was difficult for teachers to develop the students’ knowledge and behavior of defending the nation of Republik Indonesia. Several technical issues were found by both teachers and students in implementing long distance learning (online learning). Some discrepancies were also found in the learning approach, learning model, learning method and learning media. Therefore, curriculum development with special conditions (not 2013 Curriculum) is needed during the condition of emergency, for example during the Covid-19 Pandemic